OPTIMIZING THE ROLE OF BUMDES IN STRENGTHENING THE DIGITAL ECONOMY: INSIGHTS FROM THE PHILIPPINES COMMUNITY BEST PRACTISE. - Meirani Harsasi; Sahraman D. Hadji Latif; Zulfahmi; Andy Mulyana; Novita Nugraheni; I Wayan Sudiana; Komang Agus Rudi Indra Laksana (Jurnal Pengabdian Masyarakat Ekonomi dan Bisnis Digital, 2025)
This service activity aims to increase the capacity of Village-Owned Enterprises (BUMDes) in encouraging the digital economy of the community in Badung Regency, Bali, by adapting best practices from the Philippines. The methods applied include digital literacy training for BUMDes administrators and the community, the development of internet infrastructure and digital management systems, mentoring by experts from the Philippines, and multi-stakeholder collaboration between the government and the private sector. The results obtained show that the operational capacity of BUMDes that adopt technology by the community is reflected in the growth and involvement of 21 BUMDes in active collaboration in the programs implemented. However, the challenges faced in this activity include the gap in internet infrastructure which is still an obstacle, as well as the existence of cultural resistance among the community to digital-oriented change. This activity succeeded in creating an effective replication model for the sustainable development of a BUMDes-based digital economy to boost the local economy and enhance the well-being of the village community. In this context, continuous support from various parties, including local governments and the private sector, is key to overcoming existing challenges and accelerating the transformation of the digital economy in Badung Regency. This effort is expected to realize BUMDes that are more adaptive and innovative in the digital era.